ANALISIS PENERAPAN MAQĀṢID AL-SHARĪ'AH DALAM PERBANKAN SYARIAH DAN KETERKAITANNYA DENGAN MINAT MASYARAKAT DI INDONESIA - Yusuf Riyanto; Muhammad Ridha; Imron Natsir (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study analyzes the philosophical foundations and implementation of Maqāṣid al-Sharī'ah in Islamic banking in Indonesia and its linkage to public interest, using a normative-institutional approach with a Systematic Literature Review (SLR) of regulations, journals, and dissertations from 2020-2025. The findings show that Maqāṣid al-Sharī'ah functions not only as normative legitimacy but also as an instrument for social welfare, customer protection, and public trust. The integration of ESG values and the tawāzun principle contributes positively to public interest, despite challenges from low Islamic financial literacy. This study offers a conceptual framework linking maqāṣid al-sharī'ah with public interest through the pathways of ESG, tawāzun, and financial literacy, confirming that more consistent implementation strengthens Islamic banks' potential to attract public interest and their position in the national financial system.